Calcium-titanium compound recycled from titanium-containing slag and recycling method and application thereof
By controlling the specific surface area and pore structure of the perovskite composite, combined with high-temperature mineral reconstruction and multi-stage leaching treatment, the problem of recovering the perovskite phase in titanium-containing slag was solved, realizing the efficient recovery and widespread application of high-purity perovskite oxides, and reducing costs and environmental impact.
Patent Information
- Application Number
- CN202511473213.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-07-09
- Filing Date
- 2025-10-15
- Publication Date
- 2026-01-09
AI Technical Summary
Existing technologies are insufficient for the efficient recovery and utilization of the perovskite phase in titanium-containing slag, resulting in low resource utilization rates. Furthermore, traditional hydrometallurgical processes are environmentally unfriendly and pose safety risks and high acid consumption.
By controlling the specific surface area, micropore volume, and pore size of the calcium-titanium composite, high-purity calcium-titanium oxides were prepared using high-temperature mineral reconstruction and multi-stage leaching. The reaction conditions were improved by using a modifier to generate oxidizing gas at high temperature, and the purity and solubility of the calcium-titanium oxides were improved by multi-stage acid leaching to remove insoluble silicates.
It achieves efficient recovery of calcium titanium oxides with a purity of up to 99.67%, reduces acid consumption and environmental pollution, and is suitable for use in catalysts, fuel cell electrode supports and building materials, with good mechanical and thermal stability.
Smart Images

Figure CN121294854A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium-containing slag application technology, specifically relating to a calcium-titanium composite recovered from titanium-containing slag, its recovery method, and its application. Background Technology
[0002] In the metallurgical smelting process, a large amount of metallurgical slag is generated. This slag contains various valuable metals that are difficult to recover and utilize, and historically, a large amount of metallurgical slag has not been fully utilized. For example, titanium-containing blast furnace slag is a large amount of solid waste generated during the blast furnace smelting of vanadium-titanium magnetite. Its chemical composition mainly includes CaO, MgO, SiO2, TiO2, Al2O3, etc. Based on the TiO2 grade in blast furnace slag, it can be divided into low-titanium type (TiO2 < 10%), medium-titanium type (TiO2 10%~20%), and high-titanium type (TiO2 > 20%) blast furnace slag. Titanium exists in blast furnace slag in complex forms, mainly distributed in various mineral phases such as perovskite, diopside, titanium-rich diopside, spinel, and titanium carbonitride. These mineral phases have complex structures and close intergrowth relationships. Furthermore, the titanium components dispersed in the slag have fine grains and are also combined with elements such as vanadium, iron, aluminum, magnesium, and manganese, making it difficult to effectively separate and recover them using traditional beneficiation techniques. Due to technological constraints, the TiO2 content in the tens of millions of tons of titanium-containing blast furnace slag accumulated over time is as high as 25%. Therefore, the efficient utilization of these valuable titanium-containing resources is of great significance.
[0003] However, the most valuable element in titanium slag, "Ti," is dispersed in various minerals, resulting in a low content of the perovskite phase, which significantly limits its resource utilization. Numerous challenges exist in its industrial resource utilization: Firstly, the complex mineral composition of titanium-containing slag is the primary challenge for resource recovery: titanium exists in multiple mineral phases, dispersed in perovskite, titanium-bearing diopside, and zeolite, among others. The intergrowth relationships between these phases are complex, and the grain size is fine, with titanium crystals measuring only 10-15 μm, making resource utilization difficult. Furthermore, the presence of fine branches and particles in the perovskite hinders beneficiation and separation. Secondly, current hydrometallurgical processes consume a large amount of acid for titanium enrichment, which is not conducive to cost control during large-scale production and is also environmentally unfriendly.
[0004] While existing technologies have made some progress in the resource utilization of titanium-containing slag, the overall utilization rate remains low, making it difficult to achieve high-value-added, large-scale utilization. For example, Chinese patent application No. 201210004204.3, published on July 18, 2012, discloses a method for preparing CaTiO3 composite materials using slowly cooled titanium-containing blast furnace slag. The inventors mixed titanium-containing blast furnace slag with a certain amount of NaNO3 at high temperature for thermal modification, converting insoluble silicates into soluble ones. After washing with hot water to remove these silicates, the filter residue was acidified with a 5wt% dilute hydrochloric acid solution, and then filtered and washed with water to remove components such as Al, Fe, and Mg, resulting in a calcium titanium oxide content of 87%. However, NaNO3 as an additive poses industrial safety risks, and the purity of the subsequent calcium titanium oxide needs to be improved to obtain higher-purity, high-value calcium titanium oxides.
[0005] Therefore, in order to maximize the utilization of historically stockpiled titanium-containing slag with high TiO2 content, it is urgent to find a way to recover calcium-titanium composites and their recovery products from stockpiled titanium-containing slag, and their applications. Summary of the Invention
[0006] 1. The problem to be solved One of the objectives of this invention is to provide a calcium-titanium composite recovered from titanium-containing slag, with the aim of controlling the specific surface area, micropore volume, and pore size of the surface pore structure of the calcium-titanium composite.
[0007] Another objective of this invention is to provide a recycling method that increases the content of calcium and titanium oxides in calcium-titanium composites prepared from titanium-containing slag, thereby further providing applications for the aforementioned calcium-titanium composites.
[0008] 2. Technical Solution To solve the above problems, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a calcium-titanium composite recovered from titanium-containing slag, comprising calcium-titanium oxide, having a porous structure on both the surface and interior, wherein: Specific surface area is 0~30 m² 2 / g, preferably 0~10 m 2 / g, preferably 0~2 m 2 / g, preferably 2~25 m 2 / g, preferably 2~10m 2 / g; The micropore volume is greater than 0.00008 cm³. 3 / g, preferably 0.00008~0.003cm³ / g, preferably 0.00008~0.0006cm³ / g, preferably 0.00008~0.0008cm³ / g; The pore size of the pore structure is 7~100 nm, preferably 7~15 nm, more preferably 10~60 nm, and more preferably 13~95 nm.
[0009] When the above technical solution is adopted, the perovskite composite of this application is a porous material, and the specific surface area, micropore volume, and pore size of the pore structure are controlled within the above-mentioned range: On the one hand, it has low diffusion resistance in gases or liquids, making it particularly suitable for catalytic processes involving macromolecular reactants; on the other hand, its suitable specific surface area reduces adsorption sites for non-target substances, avoids excessive competition of reactants on the surface, improves the selectivity of the target reaction, and reduces byproducts. For example, in the cathode of a fuel cell, porous perovskite composites can accelerate the mass transfer efficiency of the oxygen reduction reaction.
[0010] On the other hand, the perovskite composite of this application has good mechanical and thermal stability. The suitable specific surface area means suitable pore walls and dense skeleton, excellent compressive strength, and is not easily deformed under high temperature or high pressure environment. It also has good air permeability, which is beneficial for its application as a support structure, such as electrode support for solid oxide fuel cells and building materials. At the same time, it can inhibit particle agglomeration, which is beneficial for its use as a support structure and for maintaining stable activity of catalysts during recycling, thus extending cycle life.
[0011] Finally, it is worth mentioning that the pore size of this invention can be adjusted. While ensuring the mass transfer effect, the pore volume formed by the micropores inside the perovskite composite of this application provides active sites. The synergistic effect of the two has broad application prospects.
[0012] As one possible implementation scheme, the two-stage slag has a specific surface area distribution of 0~10 m² / g, a micropore volume distribution of 0.000138~0.0006 cm³ / g, and a pore size distribution of 10~60 nm.
[0013] As one possible implementation scheme, the three-stage slag has a specific surface area distribution of 0~10 m² / g, a micropore volume distribution of 0.00008~0.0008 cm³ / g, and a pore size distribution of 13~95 nm.
[0014] As one possible implementation, the calcium titanium oxide content in the calcium titanium composite is greater than 80%, preferably greater than 90%, more preferably greater than 95%, more preferably greater than 96%, and more preferably 96.98%.
[0015] As one possible implementation, the titanium oxide content in the perovskite composite is 40-60%, preferably 50-60%.
[0016] The second aspect of this invention provides a possible method for preparing the aforementioned perovskite composite, involving resource recovery from titanium-containing slag. Due to the use of high-grade iron ore vanadium-titanium magnetite as feedstock, the TiO2 grade in existing titanium-containing blast furnace slag is lower than that in historically accumulated titanium-containing blast furnace slag. The molar ratios of Ca and Ti in historically accumulated titanium-containing blast furnace slag are 1.4:1 and 1.7:1, respectively. Therefore, a higher yield of perovskite oxides (with a 1:1 molar ratio of Ca to Ti in perovskite oxides) is expected to be obtained from historical cold slag. Furthermore, preparing the perovskite composite from cold slag can overcome the geographical limitations of its production (Panxi region), making production flexible and convenient. The specific steps are as follows: S1. Mineral Reconstruction: Modifier powder is mixed into titanium-containing slag powder, and after uniform mixing, it is calcined to carry out mineral reconstruction. Oxidizing gas may also be introduced during the process. The temperature of mineral reconstruction is controlled not lower than 1300℃, preferably 1300℃~1600℃, 1350℃~1500℃, or 1450℃~1550℃, preferably 1400℃, 1480℃, or 1550℃. After cooling, reconstructed slag is obtained, which is then crushed and / or ground to obtain reconstructed slag particles. S2, Leaching treatment: The reconstructed slag particles obtained in step S1 are subjected to at least two leaching treatments to obtain the leachate, namely the calcium-titanium complex, which includes at least one leaching treatment containing F salt or F acid.
[0017] As one possible implementation, the reaction vessel for mineral reconstruction in step S1 uses a vessel wall made of an alkaline material, including magnesium- and chromium-containing alkaline refractories such as magnesia-carbon bricks. If the vessel wall is made of an acidic material, it is prone to reacting with the modifier, affecting the degree of mineral reconstruction, reducing the enrichment of calcium titanium oxides and the formation of soluble silicates, and also causing corrosion to the vessel wall, thus affecting its service life. This application uses an unconventional method to improve the purity of the calcium titanium composite, allowing for controllable adjustment of the specific surface area and pore size over a wide range.
[0018] As one possible implementation, in step S1, the particle size of the titanium slag powder and the modifier powder is less than 200 mesh.
[0019] As one possible implementation, in step S1, the mass of the modifier is 5% to 40% of the mass of the titanium-containing slag, preferably 15% to 40% of the mass of the titanium-containing slag, preferably 15% to 35% of the mass of the titanium-containing slag, preferably 15% to 28% of the mass of the titanium-containing slag, preferably 28% to 35% of the mass of the titanium-containing slag, preferably 28% to 40% of the mass of the titanium-containing slag, and preferably 35% to 40% of the mass of the titanium-containing slag.
[0020] As one possible implementation, in step S1, the titanium-containing slag includes, but is not limited to, one or more of the following: titanium-containing blast furnace slag, ilmenite, a mixture of high-titanium slag and calcium silicate solid waste (natural mineral), ilmenite and calcium silicate solid waste (or mineral), and titanium slag (or titanium ore) and calcium silicate solid waste (or mineral).
[0021] As one possible implementation, in step S1, the modifier is a sodium- or potassium-containing compound, preferably a sodium- or potassium-containing compound that easily generates oxidizing gases, including but not limited to organic compounds and inorganic compounds. The effective components of the organic compound are one or more of sodium humate, potassium sodium humate, sodium acetate, potassium acetate, sodium benzoate, and potassium benzoate. The effective components of the inorganic compound are one or more of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, sodium nitrate, and potassium nitrate.
[0022] When using the above technical solution, the modifier is preferably a component that can generate oxidizing gas at high temperatures. For example, sodium humate will directly decompose into Na at temperatures above 400°C. + CO2, Na + The formation of insoluble silicates is interrupted; when benzoate is added to alkaline titanium-containing slag, it releases CO2 at the high temperature of mineral reconstruction; when benzoate is added to alkaline titanium-containing slag, it releases CO2 at the high temperature of mineral reconstruction; acetate decomposes into carbonate and acetone at temperatures above 400℃. Acetone is completely oxidized to CO2 and water under high temperature and oxygen-rich conditions, while carbonate releases CO2 at the high temperature of mineral reconstruction. CO2 plays a role similar to airflow stirring in the slag system, and reduces the viscosity of the slag system, resulting in good kinetic conditions and a complete reaction.
[0023] When sodium hydroxide, potassium hydroxide, sodium nitrate, or potassium nitrate are used as modifiers, mineral reconstruction can also be achieved by introducing oxidizing gas.
[0024] As one possible implementation, in step S2, a two- to three-stage leaching process is used to obtain a calcium-titanium composite, wherein the calcium-titanium oxide content in the calcium-titanium composite is greater than 86%.
[0025] As one possible implementation, step S2 employs a two-stage leaching process, with the following steps: S21, First-stage acid leaching: The reconstituted slag particles are placed in a first-stage acid, and after filtration, washing and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid is less than or equal to 0; the purpose of the first-stage acid leaching is to remove soluble silicates from the reconstituted slag; S22, Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or F acid, and after filtration, washing and drying, a second-stage leachate is obtained; wherein, the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution.
[0026] As one possible implementation, in step S21, one or more of the first-stage acid HCl, HF, HBr, HI, and HNO3 are mixed, and the mass ratio of the reconstructed residue particles to the volume of the first-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, and 80℃; the leaching reaction time is 0.5~2 h.
[0027] As a possible implementation, in step S21, when the leaching system temperature is 0°C or below, i.e. in an ice-water (or brine) bath environment, the ratio of the mass of the reconstituted slag particles to the volume of a first-stage acid is 1 g:(5~10 ml), which can increase the solid-liquid ratio and reduce the acid consumption for titanium enrichment in the prior art.
[0028] The applicant attempted to prepare a composite leachate by mixing an F-containing salt into an acid solution. However, this mixing process generates HF, which poses a significant hazard and is detrimental to large-scale industrial production. Therefore, it is essential that the acid and the F-containing salt be separated for the acid leaching treatment in this application.
[0029] As a possible implementation, in order to further strip away the unreconstructed insoluble silicates, in step S22, the mass concentration of the effective components in the leachate is 0.5%~10%. For example, when the leachate is an NH4HF2 solution, the mass concentration of the NH4HF2 solution is 0.5%~10%, and the mass ratio of a segment of leachate to the volume of the NH4HF2 solution is 1g:(5~25ml). As one possible implementation, in step S22, the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2h.
[0030] As one possible implementation, step S2 includes three leaching processes, namely: S21, First-stage acid leaching: The reconstituted slag particles are placed in a first-stage acid, and after filtration, washing and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid is less than or equal to 0; the purpose of the first-stage acid leaching is to remove soluble silicates from the reconstituted slag; S22, Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or F acid, and after filtration, washing and drying, a second-stage leachate is obtained; wherein, the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution.
[0031] S23, Three-stage acid leaching: The two-stage extract is placed in a three-stage acid, and after filtration, washing and drying, a three-stage extract, namely a calcium-titanium complex, is obtained; wherein, the pH value of the three-stage acid is greater than 0, preferably the pH value of the three-stage acid is 0.5 or 1.0.
[0032] As one possible implementation, in step S21, the first-stage acid is one or more of HCl, HF, HBr, HI, and HNO3, and the mass ratio of the reconstituted residue particles to the volume of the first-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2 h.
[0033] As a possible solution, when the leaching system temperature is 0°C or below, i.e. in an ice-water (or brine) bath environment, the ratio of the mass of the reconstituted slag particles to the volume of a first-stage acid is 1 g:(5~10 ml), which can increase the solid-liquid ratio and reduce the acid consumption for titanium enrichment in existing technologies.
[0034] As one possible implementation, in step S22, the mass concentration of the effective component in the leachate is 0.5% to 10%. For example, when the leachate is an NH4HF2 solution, the mass concentration of the NH4HF2 solution is 0.5% to 10%, and the mass ratio of a portion of the leachate to the volume of the NH4HF2 solution is 1 g:(5~25 ml). The leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2 h.
[0035] As one possible implementation, in step S23, the three-stage acid is one or a mixture of HCl, HF, HBr, HI, and HNO3. The mass ratio of the two-stage extract to the volume of the three-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, and 80℃, and the leaching reaction time is 0.5~2 h.
[0036] It should be noted that in the second-stage leaching, sparingly soluble silicates are converted into sparingly soluble fluoride salts (such as MgF2) and readily soluble silicon fluoride: MgF2 is a sparingly soluble substance (Ksp(25℃) = 5.16 × 10⁻⁶). -11 It has a stable crystal structure and reacts slowly with dilute acids at room temperature. - With H + It combines to form HF (a weak acid, pKa = 3.18), but the low solubility of MgF2 limits its dissociation rate, requiring strong acid or high temperature conditions to promote the reaction. Increasing the temperature promotes dissolution and ion diffusion; concentrated acid increases H2O. + Concentration shifts the equilibrium to the right, so a strong acid and an 80°C constant temperature water bath are preferred.
[0037] It should be noted that the leachate from the first and / or second and / or third stages of this application contains silicic acid and magnesium-aluminum metal compounds, which can be used to produce silica, magnesium-aluminum refractories (such as magnesium-aluminum spinel), etc.
[0038] The third aspect of the present invention provides the application of the above-mentioned calcium-titanium composite in the production and preparation of titanium alloys, sponge titanium, titanium tetrachloride, ceramic materials, welding materials, electronic materials, semiconductor materials, dielectric materials, catalysts (including but not limited to coal combustion sulfur and nitrogen fixation and combustion catalysts) and their carriers, coating materials, thermoelectric materials, microwave absorbing materials and other titanium-containing products.
[0039] 3. Beneficial effects Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In the preparation method of the calcium-titanium composite of the present invention, although the two main minerals, soluble silicate and enriched calcium-titanium oxide, are inter-embedded to a certain extent in the reconstructed slag particles obtained by mineral reconstruction, the average particle size of the enriched calcium-titanium oxide is greatly increased, growing from about 10 micrometers in the original titanium-containing blast furnace slag to about 30 micrometers. Therefore, the monomer dissociation of the two does not need to be less than 30 micrometers as in traditional physical separation (flotation, gravity separation or magnetic separation, etc.).
[0040] Furthermore, it is worth noting that while existing technologies have enabled the enrichment and growth of perovskite oxides to over 30 micrometers, the significant differences in physical properties between artificially enriched perovskite oxides and natural perovskite oxides result in very low physical sorting efficiency. Experimental data (leaching sample composition) indicate that by simply crushing the reconstructed slag particles to no larger than 80 mesh (approximately 100 micrometers), the subsequent leaching solution can easily dissolve the soluble silicates already formed and encapsulated or embedded in the enriched perovskite oxides (due to favorable mass transfer kinetics). In other words, the soluble silicates inside the reconstructed slag can also be leached, dissolved, and stripped away.
[0041] Simultaneously through Na + and / or K + It can inhibit the formation of insoluble silicates and form eutectic compounds with silicon dioxide: Na + K + Both methods inhibit SiO2 polymerization and reduce the formation of insoluble silicates (such as CaSiO3) by increasing the basicity of the slag; and reduce the formation of silicates (SiO4) by increasing the basicity of the slag. 4- This forms soluble complexes (such as Na₂SiO₃, K₂SiO₃, etc.), greatly reducing the tendency of silicate molecules to aggregate. It should be noted that K salt modification makes it easier to separate the reconstituted slag from the container than Na salt modification.
[0042] (2) In the preparation method of the calcium-titanium composite of the present invention, the extraction and application of calcium-titanium oxides are realized through the leaching process, and the grade of calcium-titanium oxides can even reach 99.67%; (3) In the preparation method of the calcium titanium composite of the present invention, after the three-stage acid leaching and peeling, the calcium titanium oxide obtained by filtration, washing and drying has no silicon gel coating on the surface compared with the previous patent technology, and can exert its performance to the maximum extent.
[0043] (4) In the preparation method of the calcium-titanium composite of the present invention, the raw materials used are titanium-containing slag with wide sources, including but not limited to titanium-containing blast furnace slag, ilmenite, a mixture of high titanium slag and calcium silicate solid waste (natural mineral), ilmenite + calcium silicate solid waste (or mineral), titanium slag (or titanium ore) + calcium silicate solid waste (or mineral), one or more of these, which are low in cost and do not generate secondary pollution in the whole process, thus meeting the environmental protection requirements.
[0044] (5) In the preparation method of the calcium-titanium composite of the present invention, the modifiers with effective components are acetate, benzoate, carbonate, bicarbonate, strong base salt and nitrate are used. Among them, acetate, benzoate, carbonate and bicarbonate are better than NaNO3 as alkaline heat modifiers. Since the NO gas generated during the high-temperature alkaline heat reaction of NaNO3 will cause environmental pollution, the catalyst has a high risk in the high-temperature preparation process. However, the use of acetate, benzoate, carbonate and bicarbonate, which generate weak oxidizing carbon dioxide, will not cause environmental pollution. At the same time, it plays a similar role to airflow stirring in the slag system, making the viscosity of the slag system smaller.
[0045] (6) The main principle of the preparation method of the perovskite composite of the present invention is as follows: ① Titanium-containing blast furnace slag is co-melted at high temperature with sodium and / or potassium salts that produce oxidizing gases. The modifier is used to reconstruct the pyroxene, which is insoluble in acid, into silicates that are easily soluble in acid. At the same time, the weak oxidizing gas CO2 generated by the high-temperature reaction can oxidize the low-valence state "Ti" in minerals such as diopside. Then, through thermodynamic control, the reaction of Ca and Ti in calcium titanium oxides, diopside and calcium feldspar silicate minerals such as anorthite in titanium-containing blast furnace slag is realized, thereby enriching calcium titanium oxides.
[0046] ② First, acid hydrolysis with an acid solution is used to remove most of the SiO2, Al2O3, Fe2O3 and MgO from the reconstructed residue through leaching treatment, resulting in a first-stage leaching residue; Then, in the presence of F-containing salts, such as under the reaction conditions of ammonium bifluoride, the small amount of insoluble silicates remaining in the above-mentioned leaching residue will be corroded by hydrofluoric acid or F ions into H2SiF6. H2SiF6 will dissolve in water and form H2O and SiF6 ions. SiF6 ions have high solubility and are not easy to redeprecipitate, forming fluorinated silicates, which in turn cause fluoride ions to react with metals to form water-soluble salts or complexes, removing the SiO2 and other metal oxides remaining after the first leaching stage. Finally, a three-stage dilute acid solution is used to further remove the insoluble metal halides formed by the two-stage leaching process and the trace amounts of metal oxides and other impurities exposed after removal, thereby achieving the preparation of high-purity calcium-titanium composites. Attached Figure Description
[0047] Figure 1 SEM images of the perovskite complexes in Examples 1 / 1-1 / 1-2 / 1-3 / 1-4 / 1-5; Figure 2 The isotherms (left) and BJH adsorption pore size distribution diagram (right) of the perovskite complex BET detection in Examples 1 / 1-1 / 1-2 / 1-3 are shown. Figure 3The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 1 / 1-1 / 1-2 / 1-3 are shown. Figure 4 The isotherms (left) and BJH adsorption pore size distribution diagram (right) of the perovskite complex BET detection in Examples 1 / 1-1 / 1-4 / 1-5 are shown. Figure 5 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 1 / 1-1 / 1-4 / 1-5 are shown. Figure 6 SEM images of the perovskite complexes in Examples 2 / 2-1 / 2-2 / 2-3 / 2-4 / 2-5; Figure 7 The isotherm (left) and BJH adsorption pore size distribution (right) of the perovskite complex BET detection in Examples 2 / 2-1 / 2-2 / 2-3 are shown. Figure 8 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 2 / 2-1 / 2-2 / 2-3 are shown below. Figure 9 The isotherms (left) and BJH adsorption pore size distribution diagram (right) of the perovskite complex BET detection in Examples 2 / 2-1 / 2-4 / 2-5 are shown. Figure 10 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 2 / 2-1 / 2-4 / 2-5 are shown. Figure 11 SEM images of the perovskite composites in Examples 3 / 3-1 / 3-2 / 3-3 / 3-4 / 3-5; Figure 12 The isotherm (left) and BJH adsorption pore size distribution diagram (right) of the perovskite complex BET detection in Examples 3 / 3-1 / 3-2 / 3-3 are shown. Figure 13 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 3 / 3-1 / 3-2 / 3-3 are shown. Figure 14 The isotherms (left) and BJH adsorption pore size distribution diagram (right) of the perovskite complex BET detection in Examples 3 / 3-1 / 3-4 / 3-5 are shown. Figure 15 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 3 / 3-1 / 3-4 / 3-5 are shown. Figure 16 SEM images of the perovskite complexes in Examples 4-1 / 4-2 / 4-3 / 4-4; Figure 17 The isotherm (left) and BJH adsorption pore size distribution (right) of the perovskite complex BET detection in Example 4-1 are shown. Figure 18 The isotherm (left) and BJH adsorption pore size distribution (right) of the perovskite complex BET detection in Example 4-2 are shown. Figure 19 The isotherm (left) and BJH adsorption pore size distribution (right) of the perovskite complex BET detection in Examples 4-3 are shown. Figure 20 The isotherm (left) and BJH adsorption pore size distribution (right) of the perovskite complex BET detection in Examples 4-4 are shown. Figure 21 The X-ray diffraction (XRD) spectra of the perovskite composites in Examples 4-1 / 4-2 / 4-3 / 4-4 are shown. Figure 22 X-ray diffraction image of R (reconstructed slag) prepared in Example 5; Figure 23 The image is a refined X-ray diffraction pattern of R-S3 (three-stage acid leaching residue) prepared in Example 5; Figure 24 The image shows a scanning electron microscope image of the R (reconstructed residue) prepared in Example 5. Figure 25 The X-ray diffraction (XRD) spectra of the reconstructed slag and each leaching section in Example 5 are shown. Figure 26 The images show the N2 adsorption-desorption isotherms and pore size distribution diagrams for the reconstructed slag and each leaching section in Example 5. Figure 27 The image shows a SEM image of the perovskite composite product obtained in Example 5. Figure 28 The image shown is a further magnified SEM image of the calcium-titanium composite product obtained in Example 5. Detailed Implementation
[0048] The present invention will be further described below with reference to specific embodiments.
[0049] A method for preparing a calcium-titanium complex, comprising the following steps: S1. Mineral Reconstruction: The titanium-containing slag is dried, crushed, and ground, and then passed through a 200-mesh sieve to obtain titanium-containing blast furnace slag powder with a particle size not exceeding 200 mesh. The titanium-containing blast furnace slag powder is mixed and ground with a modifier, and after being mixed evenly, it is calcined to carry out mineral reconstruction. Oxidizing gas may also be introduced during the process. The mineral reconstruction temperature is controlled to be no lower than 1300℃, preferably 1300℃~1600℃, 1350℃~1500℃, or 1450℃~1550℃, preferably 1400℃, 1480℃, or 1550℃. After cooling, the reconstructed slag is obtained, and then crushed and / or ground to obtain reconstructed slag particles. S2, Leaching treatment: The reconstructed slag particles obtained in step S1 are subjected to at least two leaching treatments to obtain the leachate, namely the calcium-titanium complex, which includes at least one leaching treatment containing F salt or F acid.
[0050] In a specific implementation, in step S1, the titanium-containing slag includes, but is not limited to, one or more of the following: titanium-containing blast furnace slag, ilmenite, a mixture of high-titanium slag and calcium silicate solid waste (natural mineral), ilmenite and calcium silicate solid waste (or mineral), and titanium slag (or titanium ore) and calcium silicate solid waste (or mineral). Since the titanium-containing slags have similar compositions, they have the same reconstruction principle in mineral reconstruction. In the embodiments of this application, titanium-containing blast furnace slag is used as an example for the experiment.
[0051] In a specific embodiment, in step S1, the modifier is one or more of the following: sodium humate, potassium humate, sodium acetate, potassium acetate, sodium benzoate, potassium benzoate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, sodium nitrate, and potassium nitrate. Since potassium acetate and sodium acetate have similar structures, sodium acetate is used as an example in this embodiment. When sodium hydroxide, potassium hydroxide, sodium nitrate, or potassium nitrate are used as modifiers, an oxidizing gas, such as CO2, O2, or air, is simultaneously introduced during the reconstruction process. In a specific embodiment, in step S1, the mass of the modifier is 5%~40%, 5%~35%, 5%~28%, 5%~20%, 5%~15%, or 5%~10% of the mass of the titanium-containing slag. In a specific embodiment, the mass of the modifier is 28% of the mass of the titanium-containing slag.
[0052] In some embodiments, in order to fully remove small amounts of unreconstructed insoluble silicates, step S2 involves a two-stage leaching process to obtain the leachate, namely the calcium-titanium complex, which includes at least one leaching process containing F salt or F acid.
[0053] Specifically: S21, First-stage acid leaching: The reconstituted slag particles are placed in a first-stage acid solution, and after filtration, washing, and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid solution is less than or equal to 0; the purpose of the first-stage acid leaching is to remove soluble silicates from the reconstituted slag. The first-stage acid is a mixture of one or more of HCl, HF, HBr, HI, and HNO3. The mass ratio of the reconstructed residue particles to the volume of the first-stage acid is 1 g:(5~25 ml). The leaching system temperature is 0~80℃, 0~60℃, 0~50℃, 0~40℃, 10~40℃, 20~35℃, 20℃, 25℃, 30℃, 35℃, or 80℃. The leaching reaction time is 0.5~2 h.
[0054] When the leaching system temperature is 0℃, i.e. in an ice-water bath environment, the ratio of the mass of the reconstituted slag particles to the volume of the first stage acid is 1g:(5~10ml), which can increase the solid-liquid ratio and reduce the acid consumption for titanium enrichment in existing technologies.
[0055] S22. Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or F acid, and after filtration, washing, and drying, a second-stage leachate is obtained; wherein the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution. The mass concentration of the effective components in the leachate is 0.5%~10%. For example, when the leachate is an NH4HF2 solution, the mass concentration of the NH4HF2 solution is 0.5%~10%, and the mass ratio of a portion of the leachate to the volume of the NH4HF2 solution is 1g:(5~25ml). The leaching system temperature is 0~80℃, 0~60℃, 0~50℃, 0~40℃, 10~40℃, 20~35℃, 20℃, 25℃, 30℃, 35℃ or 80℃, and the leaching reaction time is 0.5~2h.
[0056] In some embodiments, step S2 includes three leaching processes, namely: S21, First-stage acid leaching: The reconstituted slag particles are placed in a first-stage acid solution, and after filtration, washing, and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid solution is less than or equal to 0; the purpose of the first-stage acid leaching is to remove soluble silicates from the reconstituted slag. The first-stage acid is a mixture of one or more of HCl, HF, HBr, HI, and HNO3. The mass ratio of the reconstructed residue particles to the volume of the first-stage acid is 1 g:(5~25 ml). The leaching system temperature is 0~80℃, 0~60℃, 0~50℃, 0~40℃, 10~40℃, 20~35℃, 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2 h.
[0057] When the leaching system temperature is 0℃, i.e. in an ice-water bath environment, the ratio of the mass of the reconstituted slag particles to the volume of the first stage acid is 1g:(5~10ml), which can increase the solid-liquid ratio and reduce the acid consumption for titanium enrichment in existing technologies.
[0058] S22. Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or F acid, and after filtration, washing, and drying, a second-stage leachate is obtained; wherein the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution. The mass concentration of the effective components in the leachate is 0.5%~10%. For example, when the leachate is an NH4HF2 solution, the mass concentration of the NH4HF2 solution is 0.5%~10%, and the mass ratio of a portion of the leachate to the volume of the NH4HF2 solution is 1g:(5~25ml). The leaching system temperature is 0~80℃, 0~60℃, 0~50℃, 0~40℃, 10~40℃, 20~35℃, 20℃, 25℃, 30℃, 35℃ or 80℃, and the leaching reaction time is 0.5~2h.
[0059] S23. Three-stage leaching: To remove the sparingly soluble MgF2 generated during the second-stage leaching, the second-stage leachate is placed in a third-stage acid, and after filtration, washing, and drying, a three-stage leachate, i.e., a calcium-titanium complex, is obtained; wherein, the pH value of the third-stage acid is greater than 0, preferably 0.5 or 1.0. The three-stage acid is one or a mixture of HCl, HF, HBr, HI, and HNO3. The mass ratio of the two-stage extract to the volume of the three-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, 0~60℃, 0~50℃, 0~40℃, 10~40℃, 20~35℃, 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2 h.
[0060] In the following embodiments, the reconstructed slag is S0, the first-stage slag is S1, the second-stage slag is S2, and the third-stage slag is S3. That is, S0 (Example 1) represents the reconstructed slag obtained in Example 1, S1 (Example 1-1) represents the first-stage slag obtained in Example 1-1, S2 (Example 1-2) represents the second-stage slag obtained in Example 1-2, S3 (Example 1-3) represents the third-stage slag obtained in Example 1-3, and so on.
[0061] (I) Mineral Reconstruction In specific embodiments, the reconstructed residue S0 obtained from mineral reconstruction in Examples 1-8 is shown in Table 1:
[0062] (ii) Leaching treatment Example 1-1 Example 1-1 is the product of S0 (Example 1) after a further leaching, labeled as "S1 (Example 1-1)". The leaching conditions are as follows:
[0063] Examples 1-2 to 1-5 Using "S1 (Example 1-1)" as a sample, two-stage or three-stage leaching was continued, namely Examples 1-2 to Examples 1-5, resulting in S2 and S3 respectively:
[0064] Example 2-1 Example 2-1 is the product of S0 (Example 2) after a further leaching, labeled as "S1 (Example 2-1)". The leaching conditions are as follows:
[0065] Examples 2-2 to 2-5 Using "S1 (Example 2-1)" as a sample, two-stage or three-stage leaching was continued, namely Examples 2-2 to 2-5, resulting in S2 and S3 respectively:
[0066] Example 3-1 Example 3-1 is the product of S0 (Example 3) after a further leaching, labeled as "S1 (Example 3-1)". The leaching conditions are as follows:
[0067] Examples 3-2 to 3-5 Using "S1 (Example 3-1)" as a sample, two-stage or three-stage leaching was continued, namely Examples 3-2 to 3-5, resulting in S2 and S3 respectively:
[0068] Example 4-1 Example 4-1 is the product of S0 (Example 4) after a further leaching, labeled as "S1 (Example 4-1)". The leaching conditions are as follows:
[0069] Examples 4-2 to 4-4 Using "S1 (Example 4-1)" as a sample, two-stage or three-stage leaching was continued, namely Examples 4-2 to 4-4, resulting in S2 and S3 respectively:
[0070] Performance testing XRF analysis
[0071]
[0072] In Table 2: (1) Among the S1 obtained by leaching, Examples 1-1 / 2-1 / 3-1 / 4-1 are all slag S1 obtained after leaching with concentrated hydrochloric acid, and their calcium titanium oxide content (CaO+TiO2) reaches more than 86%; among them, Example 4-1 uses an ice water bath, which can increase the leaching solid-liquid ratio and obtain a calcium titanium oxide content (CaO+TiO2) of 88%, and the BET shows that the surface pore size is small.
[0073] (2) As can be seen from Examples 1-1 / 1-2 / 1-3 and 1-1 / 1-4 / 1-5, after the reconstructed residue is leached with concentrated hydrochloric acid in one stage, it is leached with NH4HF2 in the second stage. The content of calcium titanium oxide (CaO+TiO2) decreases. However, after leaching with dilute hydrochloric acid, the content of calcium titanium oxide (CaO+TiO2) in S3 is further increased compared with S1. This indicates that NH4HF2 removes the unreconstructed insoluble silicate covering the surface of soluble silicate, and then leaching with dilute hydrochloric acid increases the content of calcium titanium oxide (CaO+TiO2). The same is true for other Examples 2-1 / 2-2 / 2-3 / 2-4 / 2-5, 3-1 / 3-2 / 3-3 / 3-4 / 3-5, and 4 / 4-1 / 4-2 / 4-3 / 4-4.
[0074] (3) On the surface of the reconstructed slag S0, first-stage slag S1, second-stage slag S2, and third-stage slag S3 in Examples 3 / 3-1 / 3-2 / 3-3 / 3-4 / 3-5 and Examples 4 / 4-1 / 4-2 / 4-3 / 4-4, the titanium-containing slag, after mineral reconstruction, transforms the pyroxene phase, which is insoluble in acid, into silicates that are easily soluble in acid, and achieves the enrichment of calcium titanium oxides; the first-stage slag dissolves the silicates, the second-stage slag further transforms the remaining small amount of insoluble silicates into water-soluble fluorinated silicates, and finally the third-stage slag dissolves the insoluble metal halides and the very small amount of metal oxides and other impurities exposed after removal, to obtain a high-purity calcium titanium composite.
[0075] BET Analysis 1. Using the reconstructed slag S0, first-stage slag S1, second-stage slag S2, and third-stage slag S3 obtained in Examples 1 and 1-1 / 1-2 / 1-3 / 1-4 / 1-5 as samples, the specific surface area, micropore volume, and pore size were measured by BET as shown below:
[0076] As can be seen from S0 (Example 1), S1 (Example 1-1), S2 (Example 1-2), S3 (Example 1-3) or S0 (Example 1), S1 (Example 1-1), S2 (Example 1-4), S3 (Example 1-5), after the reconstructed residue undergoes a first stage of concentrated hydrochloric acid leaching, a second stage of NH4HF2 leaching, and a third stage of dilute hydrochloric acid leaching, the specific surface area decreases and the pore size increases.
[0077] 2. Using the reconstructed slag S0, first-stage slag S1, second-stage slag S2, and third-stage slag S3 obtained in Examples 2 and 2-1 / 2-2 / 2-3 / 2-4 / 2-5 as samples, the specific surface area, micropore volume, and pore size were measured by BET as shown below:
[0078] As can be seen from S0 (Example 2), S1 (Example 2-1), S2 (Example 2-2), S3 (Example 2-3) or S0 (Example 2), S1 (Example 2-1), S2 (Example 2-4), S3 (Example 2-5), after the reconstructed residue undergoes a first stage of concentrated hydrochloric acid leaching, a second stage of NH4HF2 leaching, and a third stage of dilute hydrochloric acid leaching, the specific surface area decreases and the pore size increases.
[0079] 3. Using the reconstructed slag S0, first-stage slag S1, second-stage slag S2, and third-stage slag S3 obtained in Examples 3 and 3-1 / 3-2 / 3-3 / 3-4 / 3-5 as samples, the specific surface area, micropore volume, and pore size were measured by BET as shown below:
[0080] As can be seen from S0 (Example 3), S1 (Example 3-1), S2 (Example 3-2), S3 (Example 3-3) or S0 (Example 3), S1 (Example 3-1), S2 (Example 3-4), S3 (Example 3-5), after the reconstructed residue undergoes a first stage of concentrated hydrochloric acid leaching, a second stage of NH4HF2 leaching, and a third stage of dilute hydrochloric acid leaching, the specific surface area decreases and the pore size increases.
[0081] 4. Using the first-stage slag S1, second-stage slag S2, and third-stage slag S3 obtained in steps 4-1 / 4-2 / 4-3 / 4-4 as samples, the specific surface area, micropore volume, and pore size were measured by BET as shown below:
[0082] As can be seen from S1 (Example 4-1), S2 (Example 4-2), and S3 (Example 4-3), after leaching with concentrated hydrochloric acid, NH4HF2, and dilute hydrochloric acid respectively, the specific surface area of the reconstructed residue decreased and the pore size increased. However, there was no significant pore expansion in S3 (Example 4-4), possibly because almost all the sparingly soluble components were dissolved, leading to the collapse of the network structure and a decrease in pore size and volume. In Example 4-3, the concentration of dilute hydrochloric acid in the three-stage leaching was 2%, which could increase the solid-liquid ratio to achieve cost savings.
[0083] Based on the above BET data Figure 2The N2 adsorption-desorption isotherms and pore size distributions for examples 4 / 7 / 9 / 12 / 14 / 17 / 18 / 19 / 20 show that: the specific surface area distribution of each example ranges from 0.46 to 22.77 m² / g, the micropore volume distribution ranges from 0.000084 to 0.003 cm³ / g, and the pore size distribution ranges from 7.30 to 93.07 nm; among which: The slag has a specific surface area of 2.01~22.77 m² / g, a micropore volume of 0.000117~0.003 cm³ / g, and a pore size of 7.30~14.65 nm. The two-stage slag has a specific surface area distribution of 0.49~10.36 m² / g, a micropore volume distribution of 0.000138~0.0006 cm³ / g, and a pore size distribution of 9.62~56.60 nm. The three-stage slag has a specific surface area distribution of 0.46~9.41 m² / g, a micropore volume distribution of 0.000084~0.000824 cm³ / g, and a pore size distribution of 13.46~93.07 nm.
[0084] Combining XRF and BET results, the reasons for the increase in perovskite compound content (CaO+TiO2) can be analyzed: Acid leaching removes most of the soluble silicates, creating pores and exposing more magnesium and aluminum oxides. After the second stage of leaching, a small amount of unreconstructed insoluble silicates are further stripped off. At the same time, the surface is further exposed to magnesium and aluminum oxides, which react with ammonium bifluoride to form corresponding fluoride salts. The easily soluble fluoride salts are stripped off and dissolved in the leaching solution, which further expands the pores of the sample. The insoluble fluorides form a loose structure, such as magnesium fluoride and aluminum fluoride. In the three-stage acid leaching process, the sparingly soluble fluoride is further dissolved in the leachate by a displacement reaction to form a weak acid salt (the strong acid displaces the weak acid salt).
[0085] SEM analysis Figure 1 / 6 / 11 / 16 are SEM surface morphology images of the calcium-titanium composites in each embodiment. It can be seen that after acid leaching, the sample surface is porous and loose, and the sample size decreases. It gradually changes from unevenly sized blocky particles to clustered particles. The adhering substances on the surface of the reconstructed slag are gradually removed with acid leaching, indicating that the silicates on the surface of the calcium-titanium oxide can be effectively removed by three-stage leaching.
[0086] XRD analysis From the data in Table 2 and Figure 3The X-ray diffraction images of / 5 / 8 / 10 / / 13 / 15 / 21 show that S3 obtained after three-stage wet leaching is mainly composed of CaO and TiO2, and the mineral phases detected are basically all calcium titanium oxide phases, and the grade of calcium titanium oxide can reach up to 96.98% (S3 (Example 4-3)).
[0087] The following example 5 investigates how, after alkaline thermal reconstruction of titanium-containing blast furnace slag, insoluble substances such as diopside and other mineral phases in the reconstructed slag, first-stage slag, second-stage slag, and third-stage slag are transformed into water-soluble and acid-soluble substances. The Ti in the diopside, spinel and other mineral phases combines with calcium in the silicate phase and is enriched into calcium titanium oxide phase.
[0088] Example 5 The reconstructed residue of Example 5 is denoted as R (reconstructed residue), and its mineral reconstruction parameters are as follows:
[0089] X-ray diffraction image of R (reconstructed slag) as follows Figure 22 Scanning electron microscope images such as Figure 24 The X-ray energy dispersive spectroscopy analysis is shown in Table 3.
[0090]
[0091] The R (reconstructed slag) was then crushed and ground before undergoing leaching treatment. The leaching process consisted of three stages: a first-stage HCl leaching, a second-stage ammonium bifluoride leaching, and a third-stage HCl leaching to prepare high-purity calcium titanate. The specific experimental scheme is as follows: Take 300g and pour it into 3000ml of 6% HCl solution. Place it in a 30℃ constant temperature water bath and stir to leach for 1h to remove the target component. Then filter, wash and dry to obtain R-S1 (a first-stage acid leaching residue). Then, take 100g of R-S1 (first stage acid leaching residue) and pour it into 1500mL of 3%NH4HF2 solution. Place it in a polytetrafluoroethylene beaker and put it in a 40℃ constant temperature water bath. Stir and leach for 0.5h. Then filter, wash and dry to obtain R-S2 (second stage leaching residue). Finally, 90g of R-S2 (two-stage leaching residue) was poured into 900ml of 2% HCl solution and placed in an 80℃ constant temperature water bath for stirring and leaching for 0.5h. After filtration, washing, and drying, the obtained material was designated R-S3 (three-stage acid leaching residue). Its refined X-ray diffraction analysis image is shown below. Figure 23 The content of each mineral phase in the refined XRD pattern is shown in Table 4.
[0092] Based on the X-ray energy spectrum analysis in Table 3 and Figure 24The scanning electron microscope images show that after mineral reconstruction, the mineral phases evolved into a perovskite phase (region A1), a sodium magnesium aluminum silicate phase that is easily dissolved by acid (regions A2 and A3), and a small amount of sodium calcium silicon oxide (region A2).
[0093] From the data in Table 4 and Figure 23 The refined X-ray diffraction images show that the sample obtained after three-stage wet leaching is mainly composed of CaO and TiO2, and the detected mineral phases are basically all calcium titanium oxide phases, with the calcium titanium oxide grade reaching 98.5%.
[0094] Depend on Figure 25 The X-ray diffraction (XRD) patterns of R, R-S1, R-S2, and R-S3 show that before acid leaching, R (reconstructed residue) mainly contains calcium titanium oxide phase and a small amount of zeolite phase. After three-stage acid leaching, R-S1 (first-stage acid leaching residue), R-S2 (second-stage leaching residue), and R-S3 (third-stage acid leaching residue) are all mainly composed of calcium titanium oxide phase. In addition, the calcium titanium oxide phase that was not exposed in R (reconstructed residue) gradually appeared as the silicate phase was removed during the acid leaching process; and from R-S1 (first-stage acid leaching residue) to R-S3 (third-stage acid leaching residue), the peak intensity of the main calcium titanium oxide peak at around 33.11° increased, indicating that the crystallinity of the calcium titanium oxide became higher.
[0095] BET Analysis Using the perovskite composite products (R (reconstruction residue), R-S1 (first-stage acid leaching residue), R-S2 (second-stage leaching residue), and R-S3 (third-stage acid leaching residue)) obtained in Example 5 as samples, Table 5 below details the BET specific surface area, pore volume, and average pore size of the reconstruction residue and each stage of acid leaching. As shown in Table 5, after acid leaching, the surface area increases and the pore size decreases, indicating that acid leaching can remove silicates attached to the surface of perovskite oxides. The average pore size of R-S2 is larger than that of R-S1, indicating that some of the sparingly soluble fluoride salts formed in the second-stage leaching (R-S2) are attached to the surface of perovskite oxides. However, after the third-stage leaching (R-S3), the specific area and pore volume increase, indicating that the sparingly soluble magnesium fluoride and other salts formed in the second-stage leaching (R-S2) are efficiently removed by the strong acid replacing the weak acid salts during the third-stage dilute hydrochloric acid leaching process.
[0096]
[0097] Figure 26 The diagram shows the N2 adsorption-desorption isotherms and pore size distribution of the reconstructed slag and leaching sections in Example 5. Typically, at relative pressures (P / P0) < 0.9, multilayer adsorption leads to overlapping of material isotherms; all generated samples exhibit type IV isotherms and H3 hysteresis loops, such as... Figure 26 As shown in Figure a; from Figure 26As can be seen from b, the reconstructed slag is mainly macroporous, while the pore size after acid leaching (R-S1, R-S2 and R-S3) is mainly concentrated in 2-50nm, and is mainly mesoporous.
[0098] SEM analysis Figure 27 The images show the SEM surface morphology of the perovskite composite product obtained in Example 5, in sequence: a) reconstructed slag (R), b) first-stage acid leaching sample (R-S1), c) second-stage acid leaching sample (R-S2), and d) third-stage acid leaching sample (R-S3). The figures show that after acid leaching, the sample size decreased, gradually transforming from unevenly sized blocky particles to clustered particles. Furthermore, the surface deposits of the reconstructed slag were gradually removed during acid leaching, indicating that the silicates on the surface of the perovskite oxide could be effectively removed by the three-stage leaching process.
[0099] Figure 28 The SEM images show further magnified surface morphology, sequentially labeled a) first-stage acid-etched sample (R-S1) and b) second-stage acid-etched sample (R-S2). The images demonstrate that after two stages of acid etching, the sample surface is porous and loose. This indicates that: Acid leaching removes most of the soluble silicates, creating pores and exposing more magnesium and aluminum oxides. After the second stage of leaching, a small amount of unreconstructed insoluble silicates are further stripped off. At the same time, the surface is further exposed to magnesium and aluminum oxides, which react with ammonium bifluoride to form corresponding fluoride salts. The easily soluble fluoride salts are stripped off and dissolved in the leaching solution, which further expands the pores of the sample. The insoluble fluorides form a loose structure, such as magnesium fluoride and aluminum fluoride. In the three-stage acid leaching process, the sparingly soluble fluoride is further dissolved in the leachate by a displacement reaction to form a weak acid salt (the strong acid replaces the weak acid salt). It should be noted that although almost all the sparingly soluble components in the three-stage slag are dissolved, it may cause the network structure to collapse, which in turn reduces the pore size and pore volume.
[0100] XRF analysis XRF analysis of samples after leaching in Example 5 is shown in Table 6 below.
[0101] Unless otherwise specified, the raw materials and equipment used in this invention are all commonly used in the art; the methods used in this invention, unless otherwise specified, are all conventional methods in the art. The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the invention. Any simple modifications, alterations, and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A calcium-titanium composite recovered from titanium-containing slag, characterized in that: Including perovskite oxides, which have porous structures both on the surface and inside, with a specific surface area of 0–30 m². 2 / g, preferably 0~10 m 2 / g, preferably 0~2 m 2 / g, preferably 2~25 m 2 / g, preferably 2~10 m 2 / g; The micropore volume is greater than 0.00008 cm³. 3 / g, preferably 0.00008~0.003cm 3 / g, preferably 0.00008~0.0006cm 3 / g, preferably 0.00008~0.0008cm 3 / g; The pore size of the pore structure is 7~100 nm, preferably 7~15 nm, more preferably 10~60 nm, and more preferably 13~95 nm.
2. The calcium-titanium composite recovered from titanium-containing slag according to claim 1, characterized in that: Specific surface area distribution is 0~10 m² 2 / g, micropore volume distribution is 0.000138~0.0006cm³ 3 / g, with a pore size distribution of 10~60 nm.
3. A calcium-titanium composite recovered from titanium-containing slag according to claim 1, characterized in that: Specific surface area distribution is 0~10 m² 2 / g, micropore volume distribution is 0.00008~0.0008cm³ 3 / g, with a pore size distribution of 13~95 nm.
4. The calcium-titanium composite recovered from titanium-containing slag according to claim 1, characterized in that: The calcium titanium composite contains more than 80% calcium titanium oxide, preferably more than 90%, more than 95%, more than 96%, and more than 96.98%.
5. The calcium-titanium composite recovered from titanium-containing slag according to claim 1, characterized in that: The titanium oxide content in the calcium-titanium composite is 40-60%, preferably 50-60%.
6. A method for recovering calcium-titanium complexes from titanium-containing slag, characterized in that: The steps are as follows: S1. Mineral Reconstruction: Modifier powder is added to titanium-containing slag powder, mixed evenly, and then calcined to carry out mineral reconstruction, during which oxidizing gas may be introduced; wherein, the temperature of mineral reconstruction is controlled not lower than 1300℃, preferably 1300℃~1600℃, 1350℃~1500℃, 1450℃~1550℃, 1400℃, 1480℃, 1550℃, and after cooling, reconstructed slag is obtained, which is then crushed and / or ground to obtain reconstructed slag particles; S2, Leaching treatment: The reconstructed slag particles obtained in step S1 are subjected to at least two leaching treatments to obtain the leachate, namely the calcium-titanium complex, which includes at least one leaching treatment containing F salt or F acid.
7. The recycling method according to claim 6, characterized in that: In step S1, the particle size of the titanium slag powder and the modifier powder is less than 200 mesh.
8. The recycling method according to claim 6, characterized in that: In step S1, the mass of the modifier is 5% to 40% of the mass of the titanium-containing slag, preferably 15% to 40% of the mass of the titanium-containing slag, preferably 15% to 35% of the mass of the titanium-containing slag, preferably 15% to 28% of the mass of the titanium-containing slag, preferably 28% to 35% of the mass of the titanium-containing slag, preferably 28% to 40% of the mass of the titanium-containing slag, and preferably 35% to 40% of the mass of the titanium-containing slag.
9. The recycling method according to claim 6, characterized in that: In step S1, the titanium-containing slag includes, but is not limited to, one or more of the following: titanium-containing blast furnace slag, ilmenite, a mixture of high-titanium slag and calcium silicate solid waste, a mixture of ilmenite and calcium silicate minerals, and a mixture of titanium slag and calcium silicate minerals.
10. The recycling method according to claim 6, characterized in that: In step S1, the modifier is a sodium- or potassium-containing compound, preferably a sodium- or potassium-containing compound that easily generates oxidizing gases, including but not limited to organic compounds and inorganic compounds. The effective components of the organic compound are one or more of sodium humate, potassium sodium humate, sodium acetate, potassium acetate, sodium benzoate, and potassium benzoate. The effective components of the inorganic compound are one or more of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, sodium nitrate, and potassium nitrate.
11. The recycling method according to claim 6, characterized in that: In step S2, a two- or three-stage leaching process is used to obtain a calcium-titanium complex, wherein the calcium-titanium oxide content in the calcium-titanium complex is greater than 86%.
12. The recycling method according to claim 11, characterized in that: A two-stage leaching process is employed, with the following steps: S21, First-stage acid leaching: The reconstituted residue particles are placed in a first-stage acid, and after filtration, washing and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid is less than or equal to 0; S22, Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or F acid, and after filtration, washing and drying, a second-stage leachate is obtained; wherein, the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution.
13. The recycling method according to claim 11, characterized in that: A three-stage leaching process is adopted, and the steps are as follows: S21, First-stage acid leaching: The reconstituted residue particles are placed in a first-stage acid, and after filtration, washing and drying, a first-stage leachate is obtained; wherein, the pH value of the first-stage acid is less than or equal to 0; S22, Two-stage leaching: The first-stage leachate is placed in a leachate containing F salt or acid, and after filtration, washing and drying, a second-stage leachate is obtained; wherein, the effective components of the leachate include, but are not limited to, HF and NH4HF2 solution. S23, Three-stage acid leaching: The two-stage extract is placed in a three-stage acid, and after filtration, washing and drying, a three-stage extract, namely a calcium-titanium complex, is obtained; wherein, the pH value of the three-stage acid is greater than 0, preferably the pH value of the three-stage acid is 0.5 or 1.
0.
14. The recycling method according to claim 12 or 13, characterized in that: In step S21, the first-stage acid is one or a mixture of HCl, HF, HBr, HI, and HNO3, and the mass ratio of the reconstituted residue particles to the volume of the first-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, and 80℃, and the leaching reaction time is 0.5~2 h.
15. The recycling method according to claim 14, characterized in that: In step S21, when the leaching system temperature is below or equal to 0°C, the ratio of the mass of the reconstituted residue particles to the volume of the first stage acid is 1g:(5~10ml).
16. The recycling method according to claim 12 or 13, characterized in that: In step S22, the mass concentration of the effective component in the leachate is 0.5% to 10%. For example, when the leachate is an NH4HF2 solution, the mass concentration of the NH4HF2 solution is 0.5% to 10%, and the mass ratio of a portion of the leachate to the volume of the NH4HF2 solution is 1 g:(5 to 25 ml).
17. The recycling method according to claim 12 or 13, characterized in that: In step S22, the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, or 80℃, and the leaching reaction time is 0.5~2h.
18. The recycling method according to claim 12 or 13, characterized in that: In step S23, the three-stage acid is one or a mixture of HCl, HF, HBr, HI, and HNO3, and the mass ratio of the two-stage extract to the volume of the three-stage acid is 1 g:(5~25 ml); the leaching system temperature is 0~80℃, preferably 0~60℃, preferably 0~50℃, preferably 0~40℃, preferably 10~40℃, preferably 20~35℃, preferably 20℃, 25℃, 30℃, 35℃, and 80℃, and the leaching reaction time is 0.5~2 h.
19. The application of the calcium-titanium composite according to any one of claims 1 to 5 in the production and preparation of titanium-containing products such as titanium alloys, sponge titanium, titanium tetrachloride, ceramic materials, welding materials, electronic materials, semiconductor materials, dielectric materials, catalysts, catalyst supports, coating materials, thermoelectric materials, and microwave absorbing materials.
20. The application according to claim 19, characterized in that: The catalysts include, but are not limited to, coal-fired sulfur and nitrogen fixation additives and combustion catalysts.
Citation Information
Patent Citations
Method for preparing CaTiO3 composite material from slow-cooling titanium-bearing blast furnace slag
CN102583515A